Educational Values and Sexual Difference: Reality and educational policies in the Spanish context - Carrillo, Isabel (Education Policy Analysis Archives, 2004)
This article deals with the policies promoted during the conservatiSpanish government of the partido popular and the changes implemented by the 2002 Act of Educational quality and their impact on gender issues, in particular women’s human rights. This article will contend that the Act did not guarantee equality of opportunity for women. The 2000 Act’s objective was to search for solutions to contemporary technological changes and market criteria by implementing an educational reform oriented to “review, adjust and improve the life of schools”. To do so, the conservative government proposed that “quality” was the mechanism to “reach bigger social and economical progress”. This article concludes that the new socialist government, elected in March of 2004, must introduce an alternative model for the current transition, implementing both bold and transforming measures.